Strategi Pemasaran dalam Meningkatkan Minat Konsumen di Catering Lapak Ning Icha - Rizki Wulandari; Naily El Muna; Ashlihah Ashlihah (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study aims to analyze the marketing strategy implemented by Catering Lapak Ning Icha to increase consumer purchase intention. The background of this research is the intense competition in the culinary MSME sector, particularly catering services, which demands effective and sustainable marketing strategies. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and documentation involving the business owner (represented by the operator), employees, and consumers. Data analysis was conducted using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the marketing strategy based on the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) plays a significant role in increasing consumer purchase intention. In terms of product, the catering maintains taste quality, cleanliness, and menu variety. Pricing is set affordably and competitively. Easy location access and accurate ordering and distribution processes support the place and process aspects. Promotion is carried out organically through social media and word of mouth. Additionally, friendly and professional employee service, as well as physical evidence such as a clean business environment and neat packaging, contribute to positive consumer perceptions. The implications of this study suggest that consistent and integrated marketing strategies aligned with consumer needs can effectively enhance purchase intention and customer loyalty. This research serves as a reference for culinary MSME actors in designing effective and sustainable marketing strategies.